2002
DOI: 10.1086/345798
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Ras and Extracellular Regulated Kinase in the Hyperplastic Response of Middle‐Ear Mucosa during Bacterial Otitis Media

Abstract: Hyperplasia of middle-ear mucosa (MEM) during otitis media (OM) is thought to be partially mediated by the actions of growth factors and their receptors. The intracellular pathway leading from the small G-protein Ras to the extracellular regulated kinases (Erks) often links growth factor stimulation to cellular proliferation. This study assessed whether this pathway is involved in MEM hyperplasia during bacterial OM via the activation of Erk1/Erk2 in MEM of an in vivo rat bacterial OM model. Activation was max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 57 publications
1
21
2
Order By: Relevance
“…Others have found that p38 inhibition reduces bacterially induced mucin gene expression in human ME epithelial cell lines (14). However, in our earlier studies, ERK activation was not well correlated temporally with ME mucosal hyperplasia in an animal model of OM since it occurred very early and very late in OM (24). p38 activation also occurred primarily very early in OM, with peak activation 1 to 6 h after bacterial inoculation (25).…”
contrasting
confidence: 56%
See 4 more Smart Citations
“…Others have found that p38 inhibition reduces bacterially induced mucin gene expression in human ME epithelial cell lines (14). However, in our earlier studies, ERK activation was not well correlated temporally with ME mucosal hyperplasia in an animal model of OM since it occurred very early and very late in OM (24). p38 activation also occurred primarily very early in OM, with peak activation 1 to 6 h after bacterial inoculation (25).…”
contrasting
confidence: 56%
“…We have previously shown that ME mucosal explants from the MEs of rats infected 48 h before dissection with NTHI display permanently enhanced tissue proliferation (see Fig. 1 in reference 24), which can be used as a model for bacterial enhancement of ME mucosal growth (24,25). All explants maintained a healthy appearance and remained firmly attached to the plate surface throughout the duration of the study.…”
Section: Levels Of Total Jnk and Pjnkmentioning
confidence: 76%
See 3 more Smart Citations